Squamous cell carcinoma antigen combined with HPV-16 infection in predicting high-grade squamous intraepithelial lesions of the cervix. (19th May 2022) - Zhong, Guanglei; Wang, Yuhan; Yao, Shixian; Fang, Xingyu; Lin, Rongchun; Lin, Zhongqiu; Peng, Yongpai; Yao, Tingting
Abstract: An early screening of HPV and the Thinprep Cytology Test (TCT) can effectively prevent cervical cancer. However, patients with high-grade cervical intraepithelial neoplasia usually escape current screening methods and commonly develop cervical cancer. Hence, to identify effective and specific screening methods for high-grade cervical intraepithelial neoplasia is of vital necessity. In this study, 541 patients collected in Sun Yat-Sen hospital from January 2007 to December 2016 were selected. HPV genotype detection and SCC-ag detection were done in these patients. It was found that when serum SCC-ag level exceeded over 0.39 ng/ml in HPV-16 positive patients, the sensitivity and specificity of this novel approach to predict high-grade cervical intraepithelial neoplasia could reach to 83.1% and 62.1%, respectively. The result suggested that the combination of serum SCC-ag level and HPV-16 infection could be used as a novel approach for high-grade cervical intraepithelial neoplasia screening. Impact statement: What is already known on this subject? Patients with a high-grade cervical intraepithelial neoplasia usually escape current screening methods. What do the results of this study add? When serum SCC-ag level exceeded over 0.39 ng/ml in HPV-16 positive patients, the sensitivity and specificity to predict high-grade cervical intraepithelial neoplasia could reach to 83.1 and 62.1%, respectively. What are the implications of these findings for clinical practice and/or further research? Combination of serum SCC-ag level and HPV-16 infection could be used to screen high-grade cervical intraepithelial neoplasia.